A Pragmatic Analysis Of Directive Utterances In Life As We Know It Movie's Manuscript - Saputra, Rio Ardiantama, Drs. Sigit Haryanto, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
This research studies about the pragmatic analysis of directive utterances in life as we know it movie's manuscript. The object of research paper is the movie manuscript entitled Life as we know it. The study is to analyze the directive utterance of life as we know it movie subtitling in this research by pragmatic theory. The study belongs to a qualitative study. In this method, the writer wants to describe about the linguistic form of directive utterances and the politeness. In this research paper, the writer uses data in the form of sentences taken from the Life as We Know It movie's manuscript. The data source of this research is the directive utterance in the Life as We Know It movie's manuscript. The technique of data analysis in this study is clarifying, describing, analyzing the linguistic form of directive utterance and analyzing politeness that contents in each directive utterance. The result of the study shows the following conclusion that 80 data researcher find directive uterance are expresion comanding, requesting, suggesting data, the writer finds 37 data or 49.33 % as the commanding category, 33 data or 37.33 % as the requesting category, and 10 data or 13,33 % as the suggesting category. Second, from 75 data the researcher find four politeness categories in directive utterance are bald on record, off record, positive politness,negative politness. 38 data (50.67 %) of bald on record, 8 data (10.67%) off record, 23 data (30.67%) of positive politeness, and 6 data (8.00%) of negative politeness.